Ordinary State Administrative Dispute and Positive-Fictitious decisions Dispute in Administrative Court (PTUN), In Relation to Administrative Appeal - Weda Kupita (Jurnal Dinamika Hukum, 2021)
The State Administration decisions,  is a written determination by a government official, if it is the object of a dispute in the Administrative Court, it is categorized as an "Ordinary State Administrative Dispute". PTUN is also authorized to adjudicate disputes caused by the existence of "Positive-Fictitious Decisions", which is interpreted as a silence of government officials not issuing the requested petition, then the petition is considered legally granted. The dispute is categorized as "Fictitious-Positive Decision Dispute". Before filing a lawsuit to the Administrative Court, it must first take an " Administrative Appeal ", it is determined if the authorized official does not respond (acts in silence) to Administrative Appeal, then "Administrative Appeal are deemed granted". Then there will be a juridical problem: "whether the dispute will be tried by PTUN as" Ordinary State Administrative Dispute "or as" Fictitious-Positive Decision Dispute? ". The approach method used is Normative Juridical, qualitative normative analysis method, and grammatical and systematic interpretation method. It is not yet clear whether the legal event will become an "Ordinary TUN Dispute" or a "Fictitious-Positive Decision Dispute", because it cannot be classified into the two types of disputes. Certainty is needed, because the procedural law are very different between the two types of disputes.Keyword: Ordinary Dispute, Positive-Fictitious Dispute, Administrative Appeal, Administrative Court.